Role of multiparametric magnetic resonance imaging (MRI) in focal therapy for prostate cancer: a Delphi consensus project. (16th August 2014) - Muller, Berrend G.; van den Bos, Willemien; Brausi, Maurizio; Cornud, Francois; Gontero, Paolo; Kirkham, Alexander; Pinto, Peter A.; Polascik, Thomas J.; Rastinehad, Ardeshir R.; de Reijke, Theo M.; de la Rosette, Jean J.; Ukimura, Osamu; et al.
<x xml:space="preserve">Abstract</x> Objective To define the role of multiparametric MRI (mpMRI) for treatment planning, guidance and follow‐up in focal therapy for prostate cancer based on a multidisciplinary Delphi consensus project. Materials and Methods An online consensus process based on a questionnaire was circulated according to the Delphi method. Discussion points were identified by literature research and were sent to the panel via an online questionnaire in three rounds. A face‐to‐face consensus meeting followed the three rounds of questions that were sent to a 48‐participant expert panel consisting of urologists, radiologists and engineers. Participants were presented with the results of the previous rounds. Conclusions formulated from the results of the questionnaire were discussed in the final face‐to‐face meeting. Results Consensus was reached in 41% of all key items. Patients selected for focal therapy should have biopsy‐proven prostate cancer. Biopsies should ideally be performed after mpMRI of the prostate. Standardization of imaging protocols is essential and mpMRIs should be read by an experienced radiologist. In the follow‐up after focal therapy, mpMRI should be performed after 6 months, followed by a yearly mpMRI. mpMRI findings should be confirmed by targeted biopsies before re‐treatment. No consensus was reached on whether mpMRI could replace transperineal template saturation biopsies to exclude significant lesions outside the target lesion. Conclusions Consensus was reached on a number of areas related to the conduct, interpretation and reporting of mpMRI for use in treatment planning, guidance and follow‐up of focal therapy for prostate cancer. Future studies, comparing mpMRI with transperineal saturation mapping biopsies, will confirm the importance of mpMRI for a variety of purposes in focal therapy for prostate cancer.